THE USE OF TRAINING METHOD TO IMPROVE FINE MOTOR SKILL AND COGNITIVE EARLY CHILDHOOD (The Study of Student in Group B Kindergarden Aisyiyah 1 Lebong) - Ade Fitriani; Nina Kurniah (DIADIK, 2019)
This study aims to improve children’s fine and cognitive motor skills thtough the useoftrainingmethodsinkingdergarten.Thistypeofresearchisclassroomactionresearch (PTK), with research subjects is students of group B kindergarten Aisyiyah 1 Lebong in school year 2018-2019. Total amount are 13 children, consisting 7 girls and 6 boys. This research was conducted in 3 cycles, consist of each cycle was held on one meeting, consisting of 4 stages namely 1. planning, 2. implementation, 3. Observation and 4. reflection. The data collection technique is collected by using observation. The data analysis technique using percentage formula to determine the differences between cycels with t-test. Based on the analysis of the result and discussion it is known that the use of training methods can improve fine motor skills and cognitive at the age of kindergarten. Based on these references, it is recommended for the next researcher to also carry out the same research with this research, but in the material, procedures, and abilities that are expected to bedifferent.THE USE OF TRAINING METHOD TO IMPROVE FINE MOTOR SKILL AND COGNITIVE EARLY CHILDHOOD(The Study of Student in Group B Kindergarden Aisyiyah 1 Lebong)